Health assessment and parasites of willow grouse (Lagopus lagopus) in Sweden - Dæhlen, Stine Anett (SLU/Parasitology and Virology, 2003)
A clinical examination of 530 willow grouse (Lagopus lagopus) was performed between 1989 and 2002 from four different areas in the northern part of Sweden. The result show that 90 % of the birds were infected with parasites and eight species of parasites were identified from the intestines. Only three species occurred in high numbers; the coccidian Eimeria sp., the nematode Ascaridia compar, and the cestode Hymenolepis sp. The average bodyweight of the birds varied significantly between the years and primarily for the juveniles. Statistical analyses indicated that that there was a significant negative effect of both Eimeria sp. and A. compar on the bodyweight, but only in juvenile birds. Neither ectoparasites nor bloodparasites were found, and Campylobacter spp. were not isolated in this study.